2019
DOI: 10.5539/ijbm.v14n12p42
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Applications: A Model of Technology Adoption in the Grocery Setting

Abstract: One of the most discussed topics in the academic literature is the adoption of new technologies by consumers. However, researchers conducted few studies on the adoption of mobile apps for grocery shopping. Particularly, the few researches carried out focused on the adoption of mobile commerce by consumers, while no study was concerned with the use of mobile applications out-of-store, as means for shopping preparation or in-store, as tools for self-regulation. Since individuals are becoming increasingly reliant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The finding that attitudes have a positive effect on behavioral intention (H4) supports past studies [67,68]. These studies found that consumers' attitudes toward using mobile apps are an important factor in grocery trade.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The finding that attitudes have a positive effect on behavioral intention (H4) supports past studies [67,68]. These studies found that consumers' attitudes toward using mobile apps are an important factor in grocery trade.…”
Section: Discussionsupporting
confidence: 84%
“…It is then expected that, if consumers' assessment of buying online is positive, consumers' intention to buy through online stores will increase [66]. Aiolfi and Bellini examined the use of mobile apps in grocery trade and found that the factors influencing consumers' attitudes toward the adoption of apps were catalysts for business success [67]. Kokkonen and Laukkanen found that the frequency of mobile grocery app use had a significant effect on the money spent in retail stores [68].…”
Section: Decision-making Process Of Mobile Grocery Shoppingmentioning
confidence: 99%
“…Perceived usefulnessattitude towards smart speakers Over time, several studies demonstrate the validity of the TAM model in providing a useful model for researchers to analyse the cause of rejection or acceptance of a technology (Aiolfi and Bellini, 2019). The TAM model suggests how the Perceived Usefulness (PU) and the Perceived Ease of Use (PEOU) are the two determining factors for the adoption of any Smart speakers' usage intention technology that directly impact the attitude of use of a technology and, therefore, indirectly on the intention to use it.…”
Section: Smart Speakers' Usage Intentionmentioning
confidence: 99%
“…Cronbach' alpha CR AVE Perceived usefulness: Adapted by Aiolfi and Bellini (2019) 1. I believe that using a smart speaker makes my life easier 2.…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation